2022
DOI: 10.1029/2021gl097408
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductivity of Clayey Rocks and Soils: A Non‐Linear Model

Abstract: Electrical conductivity of different rocks and soils lays the base for electrical logging and electrical and electromagnetic (E&EM) methods that have been extensively used for near-surface, environmental, and hydrogeological investigations (e.g., Glover, 2015). It is the pioneering work of Archie (1942) that makes the quantitative assessment of porosity available and paves the way for other petrophysical parameters. Several years later, Patnode and Wyllie (1950) found that Archie's law is only suitable to "cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Considering reported groundwater electrical conductivities with a mean of 0.3 S/m in the area (Burnside et al., 2021), the most widely distributed observed bulk conductivities within C1 ( σ = 0.1–0.2 S/m) would require an unreasonably large fluid fraction within C1 (see Text S6.2 in Supporting Information S1). It is thus likely that enhanced conductivities in C1 are attributed to a superposition of pore fluid conduction and conduction through a conductive soil component such as clays (e.g., Pride, 1994; Qi & Wu, 2022). Clays also form through rock weathering processes and are commonly found in soils around the study area (Fritzsche et al., 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Considering reported groundwater electrical conductivities with a mean of 0.3 S/m in the area (Burnside et al., 2021), the most widely distributed observed bulk conductivities within C1 ( σ = 0.1–0.2 S/m) would require an unreasonably large fluid fraction within C1 (see Text S6.2 in Supporting Information S1). It is thus likely that enhanced conductivities in C1 are attributed to a superposition of pore fluid conduction and conduction through a conductive soil component such as clays (e.g., Pride, 1994; Qi & Wu, 2022). Clays also form through rock weathering processes and are commonly found in soils around the study area (Fritzsche et al., 2007).…”
Section: Resultsmentioning
confidence: 99%
“…According to the TDR measurements, in most parts of the lake the sediment electrical conductivity is about 0.003–0.004 S/m—higher than that of water (0.0016 S/m). This higher conductivity is probably due to the presence of ions on the surface of clay‐size grains (Qi & Wu, 2022; Ward, 1990). In two small areas (a few square meters) in the very proximity of the inflows, the electrical conductivity of the sediment is lower than the average 0.003–0.004 S/m (Figure 4d).…”
Section: Discussionmentioning
confidence: 99%
“…Data used in this study can be found in the previously published literature of Börner (1992), , Slater and Glaser (2003), Mendieta et al (2021), and Waxman and Smits (1968). Materials for the models and results presented in this paper are available in Qi and Wu (2023).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…BHS model (Bruggeman, 1935; Hanai, 1960; Sen et al., 1981) σ=σwϕm1σc/σw1σc/σm ${\sigma }^{\ast }={\sigma }_{\mathrm{w}}{\phi }^{m}{\left(\frac{1-{\sigma }_{\mathrm{c}}^{\ast }/{\sigma }_{\mathrm{w}}}{1-{\sigma }_{\mathrm{c}}^{\ast }/{\sigma }^{\ast }}\right)}^{m}$ is an exceptional precedent that can both explain real and quadrature nonlinearities concurrently, and it downscales to Archie's law when in the one‐phase situation. Compared to such an eminent model, as discussed in Qi and Wu (2022), Equation 9 bears the advantages of mathematical simplicity and parametric consistency with Archie's law. The former is because BHS is an implicit function with σ * on both sides that needs complicated methods to solve (Glover et al., 2010; Lesmes & Morgan, 2001), while the latter results from its parameter m links to both bulk and surface continuity (de Lima et al., 2005; Niwas et al., 2006, 2007).…”
Section: Comparisons With Other Modelsmentioning
confidence: 99%
See 1 more Smart Citation